PENGARUH SISTEM CASHLESS PAYMENT SEBAGAI SARANA TRANSAKSI UTAMA DI PONDOK MODERN TAZAKKA - darmawan, rizky; Shulthoni, Muhammad; Stiawan, Drajat (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research aims to analyze the perceptions of Pondok Modern Tazakka students regarding the existence of cashless payments. This research uses a qualitative descriptive method using data collection in the form of primary and secondary data. Primary data was taken from interviews with students and alumni of Pondok Modern Tazakka. And secondary data was taken from the website berita.batangkab.go.id. The research results showed that the cashless system was quite helpful for students in carrying out transactions every day at the boarding school. Financial transactions that no longer use currency (either metal or paper) are called cashless. This can be seen from the responses of students and alumni of Pondok Modern Tazakka, who responded positively to the cashless payment system implemented at the boarding school. Cashless is an example of a Westernized form of transaction that eliminates the tradition of transactions using cash, either metal or paper. Transactions here only involve scanning the card for every food or drink purchase. This cashless system is very effective; apart from being able to introduce students to digitalization, it can also minimize money loss. The cashless society phenomenon is considered quite successful among millennials and students.